Analysis of the Development of the State Civil Apparatus Candidates for Judges Behaving Negatively in Realizing the Great Justice in Indonesia - Apriliana, Shinta Devi; Pratama, Erry; Mashuri, Moch. Ali (VJJ, 2020)
The State Civil Apparatus (ASN) is an important element in carrying out the tasks of government and development in a country. In implementing governance and development, professional ASNs are needed, free from political intervention, free from corrupt, collusion and nepotism practices, able to provide public services to the community and able to play a role as the glue of national unity and integrity based on Pancasila and the 1945 Constitution. as a tool requires guidance to improve the quality of human resources to work effectively and efficiently in providing services. the services provided to the community must be fair and comprehensive, especially in terms of providing services based on community rights so that justice in Indonesia can be realized. The State Civil Apparatus (ASN) prospective judges in Indonesia who are competent in carrying out their duties and functions will create a great court without negative attitudes or arbitrary actions of an officer. The State Civil Apparatus (ASN) guidance for prospective judges is important to improve the quality of ASN's work. The purpose of this paper is to identify the ASN model for prospective judges in realizing a large judiciary in Indonesia. This study uses a literature review method which is a research method by studying the literature or primary data sources used in research. From the results of research and data analysis, it can be determined that The State Civil Apparatus (ASN) coaching for prospective judges in Indonesia uses a coaching model based on employee discipline through the level of punishment from severe, moderate, and mild. See the position of Judge more priority to integrity than intelligence. Intelligence can be increased through various education and training programs. While morality which is the nature and basic nature can not be formed and improved. So prospective judges who behave despicably must be fired in order to realize a great court in Indonesia.